The Role of Worldviews in Predicting Support for Recreational Cannabis - Sammut, Gordon; Mifsud, Rebekah; Brockdorff, Noellie (Frontiers in Psychology, 2022)
We studied the role of worldviews in the endorsement of proposals for the legalisation of recreational cannabis. Drawing on literature on generalized belief structures, we developed categorical measures for five worldviews drawing on commonalities in the typologies reviewed (Orthodox, Localized, Reward, Pragmatist and Survivor). We proceeded to study the relative influence of worldviews in support of a range of items concerned with the legalisation of recreational cannabis amongst a randomly generated sample (N=1000) in Malta. Our findings demonstrate that the Orthodox worldview stands in contrast to all others in opposing the proposals and constitutes the resistance group to legalisation. On the other hand, no other worldview unilaterally supports the proposals albeit these are, on an individual basis, favourably perceived. Our study further demonstrates that proportions of variance accounted for by the worldview measures we adopted are comparable to those exercised by demographic variables demonstrating significance. We propose that the study of worldviews is critical in understanding social and political alliances that come together to support or oppose particular politicised projects or collective courses of action.